PROXIMATE ANALYSIS, MINERAL, AND PHYTOCHEMICAL CHARACTERIZATION OF RESIDUAL SEEDS AND PODS OF PIGMENT EXTRACTED ANNATTO (BIXA ORELLANA L.) - Aluko, Ebenezer Olanrewaju; Adetuyi, Abayomi Olagundoye; Omotoso, Ezekiel (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
In natural dye extraction, plant residues are often discarded, raising environmental and sustainable practices concerns. This study therefore aimed to evaluate the nutrient, mineral, and phytochemical profiles of residual seeds and pods from Bixa orellana after pigment extraction for the purpose of waste management. Proximate analysis revealed significant differences between seeds and pods in moisture, ash, protein, crude fibre, and carbohydrate contents, while fat content showed no significant variation. The seeds contained moisture (6.32±0.10%), ash (4.10±0.29%), crude fat (4.10±0.08%), crude protein (16.31±0.04%), crude fibre (11.67±0.10%), and carbohydrates (57.48±0.50%), while the corresponding values for the pods were 9.05±0.03%, 3.40±0.21%, 4.35±0.11%, 10.52±0.04%, 41.63±0.20%, and 31.05±0.15%, respectively. Mineral analysis showed high concentrations of magnesium (12.003 mg/g) in seeds and calcium (52.011 mg/g) in pods, while chromium was absent in seeds but detected in pods (0.002 mg/g). Phytochemical analysis revealed alkaloids as the most abundant compound in both seeds (8.9±1.6 mg/g) and pods (7.2±0.4 mg/g), while flavonoids were the least (1.8±0.1 mg/g and 1.3±0.1 mg/g, respectively). ANOVA revealed significant differences (p < 0.05) in the proximate, mineral and phytochemical compositions, highlighting the nutritional and bioactive potential of both seeds and pods residues. These findings suggest that residual seeds and pods of Bixa orellana are valuable, rich in nutrients and minerals resources with potential applications in the food and pharmaceutical industries, promoting waste valorization and sustainability.